Peningkatan Hasil Belajar Materi Tanggung Jawab dalam Pembelajaran PKn Melalui Pembelajaran Aktif Tipe Role Reversal Question Peserta Didik Kelas V - Armandha, Bryan Afri; Daryanto, Joko; Matsuri, Matsuri (Didaktika Dwija Indria, 2026)
The study aimed to describe the improvement in learning outcomes on responsibility material in Civics for fifth-grade students of SD N 2 Tambakan Klaten using the Pembelajaran aktif Role Reversal Question Type Model. This collaborative Classroom Action Research involved 13 students, with the teacher as the implementer and the researcher as the observer. Conducted in two cycles, data were collected through tests, observations, and documentation and analyzed quantitatively and qualitatively. Success was defined as ≥75% of students scoring ≥70. In the pre-action stage, the average score was 53.84, with 1 student (7.69%) achieving ≥70, while 12 students (92.31%) scored below. In Cycle I, the average increased by 10% to 64.61, and the proportion of students scoring ≥70 rose to 23.08%. In Cycle II, the average improved by 11% to 76.15. The study concluded that the Role Reversal Question Model effectively enhanced learning outcomes. The steps include preparing material-based questions, explaining activities, dividing students into groups, assigning group discussions, creating individual questions, conducting role-reversal Q&A sessions, and providing feedback.